The post-brexit legal framework for international migration in the UK: Differentiated deportability of poor europeans? - Agnieszka Radziwinowiczówna; Olayinka Lewis (University of Warsaw, Centre of Migration Research (CMR), 2021)
Politicians often mention immigration enforcement, and deportation in particular, as a means to assert state sovereignty. The scholarship on deportation in philosophy and political anthropology also names exclusion as a founding act of sovereignty. This paper looks at deportation through an event that is interpreted as regaining sovereignty by a State, that is exiting a supra-national political organization, namely the European Union. New immigration regulations in the UK are meant to end the EU Freedom of Movement and equalise the statuses of EU- and non-EU migrants in the UK. The research question this working paper addresses is the following: how will the new immigration regulations and policies affect the possibility of deportations of EU citizens in the UK? With the lens of Interpretive Policy Analysis, the working paper analyses primary sources, such as regulations, policy papers and policy implementation guidelines as well as expert interviews with immigration advisors. It concludes that the deportability of EU citizens will increase. Deportability of EU citizens will be differentiated, as rough sleepers, former convicts and irregular migrants may be first to be targeted with deportation and form a new deportspora.
Keywords: 330; Brexit; EU citizens; EU Settlement Scheme; deportation; deportability; sovereignty; legal analysis; differentiated deportability; exclusion